Sub-Block Aided OFDM with Index Modulation - ACAR, YUSUF (Bajece (İstanbul Teknik Üniversitesi), 2019)
Recently, orthogonal frequency division multiplexing (OFDM) with index modulation (IM) has been appeared as a novel method for future wireless communication systems. However, such a mechanism has low spectral efficiency since some sub-carriers are not activated in order to implicitly convey information. In this paper, a subblock dependent approach, called sub-block aided OFDMIM (SA-OFDM-IM) technique, is proposed for spectral efficiency enhancement of the OFDM-IM method with lower complexity. The simulation results illustrate that the proposed SA-OFDM-IM and well known OFDM-IM have same bit error rate (BER) performance while SA-OFDMIM has 40% more spectral efficiency with low complexity.
Keywords: Orthogonal Frequency Division Multiplexing (OFDM); Index Modulation (IM); Spatial Modulation (SM)